Humility and Inquiry: A Response to Tibor Solymosi - Mark Tschaepe (Eidos. A Journal for Philosophy of Culture, 2019)
In his essay, “Affording our Culture: “Smart” Technology and the Prospects for Creative Democracy,” Tibor Solymosi addresses my challenge for neuropragmatism to counter what I have elsewhere called dopamine democracy. Although I believe that Solymosi has begun to provide an explanation for how neuropragmatism may counter dopamine democracy, especially with his conceptions Œ and cultural affordances, I respond with a helpful addition to his approach by returning to the theory of inquiry as put forth by John Dewey. In particular, I focus on the phases of inquiry as colored by Dewey’s concept of humility. Solymosi does not pay adequate attention to the function of inquiry necessary for combatting dopamine democracy. His account of cultural affordances and education is strengthened by using Dewey’s concept of humility as a guiding disposition for neuropragmatic inquiry. Recognizing humility as an instrument of neuropragmatic inquiry provides us with a tool to better address the pitfalls of dopamine democracy, especially misinformation and incentive salience. My argument proceeds by first articulating dopamine democracy as a problem and Solymosi’s concept of cultural affordances and how he understands these as neuropragmatic tools to address the problem through education. I present humility as an instrumental concept derived from Dewey’s work on inquiry. I then suggest how humility may serve neuropragmatic inquiry to assist in combatting the problems of dopamine democracy.